The Correlation Between Grit and Work Readiness of UPN Veteran Jawa Timur Students - Afinatus Nur Aisyah; Azmi Listya Anisah; Nuruni Ika Kusuma Wardani (Economos : Jurnal Ekonomi dan Bisnis, 2025)
This study is to analyze the correlation between grit, which refers to an individual's perseverance and resilience, and work readiness among students of Universitas Pembangunan Nasional (UPN) Veteran Jawa Timur. The population of this research includes management students from the 2021 and 2022 cohorts. The study employed a quantitative method by conducting a survey involving 223 respondents. The data collection procedure utilized the Grit Scale developed by Duckworth et al. (2007), with a reliability coefficient of α = 0.854, and the Work Readiness Scale based on the theory of Caballero et al. ( 2011), with a reliability coefficient of α = 0.883. The research findings indicate that grit has a positive and significant relationship with work readiness, with r = 0.577 and p < 0.01. The majority of respondents demonstrated a high level of grit, with 61% falling into this category. This high level of grit contributes to better individual work readiness, specifically in areas such as social intelligence, organizational acumen, work competence, and personal characteristics. In conclusion, students with a higher level of grit tend to have better work readiness, particularly in overcoming challenges in the workplace.